2019
DOI: 10.1177/0887302x19873437
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Artificial Intelligence in Fashion: Are Consumers Ready?

Abstract: Given the growing interest in combinations of fashion and digital innovations, it is critical for both researchers and retailers to understand how consumers respond to new technologies, especially artificial intelligence (AI). The purpose of the study was to examine consumers’ attitudes and purchase intention toward an AI device. By adapting the technology acceptance model, a conceptual model was constructed and tested related to consumers’ attitudes and purchase intention toward an AI device—Echo Look. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 48 publications
4
72
1
2
Order By: Relevance
“…When they evaluate a product, they do it more smoothly [40] and they are less sensitive to price. Highly involved individuals are more voluntarily and actively engaged in fashion-related activities-e.g., reading fashion news frequently or trying new fashion-related technologies [41]. Through the research of Celik and Kocaman [42], it was confirmed that fashion involvement can significantly impact technological readiness.…”
Section: Fashion Involvementmentioning
confidence: 90%
“…When they evaluate a product, they do it more smoothly [40] and they are less sensitive to price. Highly involved individuals are more voluntarily and actively engaged in fashion-related activities-e.g., reading fashion news frequently or trying new fashion-related technologies [41]. Through the research of Celik and Kocaman [42], it was confirmed that fashion involvement can significantly impact technological readiness.…”
Section: Fashion Involvementmentioning
confidence: 90%
“…And the usage of AI based applications does not stop there: in the entertainment industry, music (AIVA, n.d.), movies (Rondinella, 2016), and even artwork (Hildebrand, 2015) is now created using the help of AI. Furthermore, fields like quantum mechanics (Duniko & Briegel, 2018), agriculture (Jha et al, 2019), housing (Callaghan et al, 2001), chemistry (de Almeida et al, 2019), education (Zawaki-Richter et al, 2019), sports (Bartlett, 2006), and fashion (Liang et al, 2020) are all benefiting from AI. Usage of AI based applications is on a steep increase, with estimates suggesting that by the year 2023, around eight billion digital voice assistants will be in use globally (Virtual Assistant Technology -Statistics & Facts, 2020).…”
Section: Artificial Intelligence Applicationsmentioning
confidence: 99%
“…AES standard is an important criterion for consumers to evaluate clothing because clothing is an important means of visual communication. 29 AES of clothing includes color, style, design, and other elements. AES attributes of clothing, such as color, style, and fabric, are the most important criteria for women to purchase clothing.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%